In vivo subcellular localization of Mal de Río Cuarto virus (MRCV) non-structural proteins in insect cells reveals their putative functions - Maroniche, Guillermo Andrés; Mongelli, Vanesa Claudia; Llauger, Gabriela; Alfonso, Victoria; Taboga, Oscar Alberto; Del Vas, Mariana (Elsevier, 2019)
The in vivo subcellular localization of Mal de Río Cuarto virus (MRCV, Fijivirus, Reoviridae) non-structural proteins fused to GFP was analyzed by confocal microscopy. P5-1 showed a cytoplasmic vesicular-like distribution that was lost upon deleting its PDZ binding TKF motif, suggesting that P5-1 interacts with cellular PDZ proteins. P5-2 located at the nucleus and its nuclear import was affected by the deletion of its basic C-termini. P7-1 and P7-2 also entered the nucleus and therefore, along with P5-2, could function as regulators of host gene expression. P6 located in the cytoplasm and in perinuclear cloud-like inclusions, was driven to P9-1 viroplasm-like structures and co-localized with P7-2, P10 and α-tubulin, suggesting its involvement in viroplasm formation and viral intracellular movement. Finally, P9-2 was N-glycosylated and located at the plasma membrane in association with filopodia-like protrusions containing actin, suggesting a possible role in virus cell-to-cell movement and spread.